2021
DOI: 10.3390/jcm10143170
|View full text |Cite
|
Sign up to set email alerts
|

Localized Atrial Tachycardia and Dispersion Regions in Atrial Fibrillation: Evidence of Spatial Concordance

Abstract: Introduction: During atrial fibrillation (AF) ablation, it is generally considered that atrial tachycardia (AT) episodes are a consequence of ablation. Objective: To investigate the spatial relationship between localized AT episodes and dispersion/ablation regions during persistent AF ablation procedures. Methods: We analyzed 72 consecutive patients who presented for an index persistent AF ablation procedure guided by the presence of spatiotemporal dispersion of multipolar electrograms. We characterized sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Spatial concordance was recently shown using spatiotemporal EGM dispersion between AT locations and AF driver sites. 19 Previously, Baykaner et al 2 using basket recordings, and Yamashita et al 3 using electrographic imaging (ECGI), showed that AT in patients with AF arose at sites that also had harboured ablation termination sites for AF. Our study further advances this concept by revealing how AT-like regions in AF may affect AF treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial concordance was recently shown using spatiotemporal EGM dispersion between AT locations and AF driver sites. 19 Previously, Baykaner et al 2 using basket recordings, and Yamashita et al 3 using electrographic imaging (ECGI), showed that AT in patients with AF arose at sites that also had harboured ablation termination sites for AF. Our study further advances this concept by revealing how AT-like regions in AF may affect AF treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be ruled out that misclassification of atrial fibrillation and EAT in the clinic affects these results; however, previous studies have also shown a close association between atrial fibrillation and EAT. [ 16 , 17 ] A possible explanation for the increasing age could be that younger patients compared to older patients tend to opt out CA due to the risk of severe complications as AV blockage and need for pacemaker after the procedure. However, our results reenforces the encouraging trend that ablation in clinical practice is considered an effective treatment regardless of age and comorbidity.…”
Section: Discussionmentioning
confidence: 99%